Using Web Data for Measuring the Effectiveness of an E-Commerce Site - Carneiro, Ana Isabel Ribeiro (2008)
An electronic commerce web site is successful if it achieves the purpose why it was created. Being successful is a necessary condition for the continuity of the business. For a company owning an e-commerce site it is not enough to know that they are selling and making a profit out of their activity; it is important to understand how they are doing it and how they can improve in order to do better and fight the competition. In this dissertation we apply the measure of the success of a web site to a real case, determining the pages which are not so successful and need a little more attention. We then determine the success measures within the customer sessions, understanding what are the more problematic pages among the buying customers. We segment the customers according to sales and navigation behaviour; this allows us to define customized marketing approaches. We make a comparison between the sales data and the success data; subsequently we determine outliers.